Obiettivi di esito e di processo in psicoterapia: dalle ricerche della Menninger School alla teoria della nascita di Massimo Fagioli - Esposto, Eleonora (Il sogno della farfalla, 2025)
This paper investigates the potential changes resulting from psychotherapeutic interventions (outcomes) and elucidates the mechanisms through which these changes are realized (processes). The article initially analyses the findings and conclusions derived from the foundational Psychotherapy Research Project (PRP) conducted by the Menninger Foundation, with particular emphasis on the operational definitions of psychic structure and structural change. These constructs are subsequently contextualized within the framework of therapeutic mechanisms – namely, analytic, supportive, and expressive modalities – through which changes are thought to occur. The discussion is further situated within the current scholarly discourse concerning the relative significance of specific versus common therapeutic factors, such as the therapeutic alliance and empathy, through a critical review of relevant empirical literature. Ultimately, the paper presents an innovative perspective on psychic structure and therapeutic determinants as proposed by Massimo Fagioli’s Human Birth Theory, proposing potential pathways for its integration and empirical validation within contemporary psychodynamic research.